Expression Profiles and Interaction of MicroRNA and Transcripts in Response to Bovine Leukemia Virus Exposure - Ma, Hao; Lippolis, John D.; Casas, Eduardo (Frontiers in Veterinary Science, 2022)
Bovine leukemia virus (BLV) infection in cattle is omnipresent, which causes significantly economical losses worldwide. The objective of this study was to determine microRNA (miRNA) and transcript profiles, and to establish their relationship in response to exposure to the virus. Small non-coding and messenger RNA were extracted and sequenced from serum and white blood cells (WBC) derived from seven BLV seropositive and seven seronegative cows. Transcriptomic profiles were generated by sequencing RNA libraries from WBC. Bta-miR-206 and bta-miR-133a-3p were differentially expressed in serum (P < 0.05). In WBC, bta-miR-335-3p, bta-miR-375, and bta-novel-miR76-3p were differentially expressed (P < 0.03). There were 64 differentially expressed transcripts (DETs). Gene ontology (GO) analysis of the DETs overexpressed in the seropositive group with GOs response to stimulus and immune system process, predicted that the DETs could potentially negative regulate viral life cycle and viral entry or release from host cells. In addition, the DETs depleted in the seropositive group could play a role in down-regulation of antigen processing and presentation of endogenous peptide antigen via MHC class I. The differentially expressed miRNAs targeted 17 DETs, among which the expressions of bta-miR-133a-3p and bta-miR-335-3p were significantly negative correlated with the expressions of ENSBTAT00000079143 and ENSBTAT00000066733 respectively. Under high prediction criteria, 90 targets of the differentially expressed miRNAs were all non-DETs. The most enriched biological process gene ontology term of the targets was the RNA-dependent DNA biosynthetic process, which could be associated with virus replication. These results suggested that the differentially expressed miRNAs fine-tune most of the target genes in responding to BLV exposure. In addition, Bta-miR-206 interacted with BLV regulatory genes rex and tax by targeting their coding regions. A further study of the miRNAs and the genes may reveal the molecular mechanisms of BLV infection and uncover possible ways to prevent the infection.